Cultivating Success: The Interplay of Innovation Marketing, Marketing Orientation and Internal Strategies on Organization Performance in Pakistan - Saleem, Kashif; Younas, Asifa (Advances in Social Sciences Research Journal, 2024)
This study's primary goal is to ascertain how innovative marketing and market-oriented internal marketing relate to one another and how this relationship affects performance in the mediating impact of innovative capability within Pakistan. To analyze the relationship between variables and accomplish the study's objective, 295 university student samples were used. The study's findings indicate that internal marketing plays a significant role in performance, meaning that an increase in internal marketing will improve an organization's performance. Innovative cultures have a big impact on how well an organization does; in Pakistan, any organization that has a strong creative culture will perform even better. Market orientation is also crucial for any organization. The study found that innovation is believed to have a mediating role in the relationship between market orientation and marketing performance.